Complement component C1q enhances invasion of human mononuclear phagocytes and fibroblasts by Trypanosoma cruzi trypomastigotes. - Rimoldi, M T (1989)
Internalization and infectivity of Trypanosoma cruzi trypomastigotes by macrophages is enhanced by prior treatment of parasites with normal human serum. Heating serum or removing C1q from serum abrogates the enhancement, but augmentation of attachment and infectivity is restored by addition of purified C1q to either serum source. Although both noninfective epimastigotes (Epi) and vertebrate-stage tissue culture trypomastigotes (TCT) bind C1q in saturable fashion at 4 degrees C, internalization by monocytes and macrophages of TCT but not Epi-bearing C1q is enhanced in comparison to untreated parasites. Adherence of human monocytes and macrophages to surfaces coated with C1q also induces a marked enhancement of the internalization of native TCT. C1q enhances attachment of both Epi and TCT to human foreskin fibroblasts, but only when C1q is on the parasite and not when the fibroblasts are plated on C1q-coated surfaces. Only TCT coated with C1q show enhanced invasion into fibroblasts. Although trypomastigotes produce an inhibitor of the complement cascade which limits C3 deposition during incubation in normal human serum, C1q binds to the parasite and enhances entry of trypomastigotes into target cells.